Megan's birthday tree : a story about open adoption - Lears, Laurie; Farnsworth, Bill (Morton Grove Ill. : A. Whitman, 2005)
Every year on Megan's birthday, her birth mother, Kendra, sends a picture of the tree she planted the day Megan was born, so when Kendra decides to get married and move to a new house, Megan worries that she will be forgotten.
3.0
K-3
Keywords: Adoption -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Moving, Household -- Juvenile fiction; Trees -- Juvenile fiction; Adoption -- Fiction; Mothers and daughters -- Fiction; Moving, Household -- Fiction; Trees -- Fiction; Adoption -- Fiction; Mother-daughter relationship -- Fiction; Moving -- Fiction; Trees -- Fiction